Monday

March 2, 2015

March 2, 2015

Posted by **Abhi** on Thursday, June 14, 2012 at 1:43pm.

- Maths -
**MathMate**, Thursday, June 14, 2012 at 5:44pmHint:

write equation as:

tan(a)=(x²-y²)/(x²+y²)

Cross multiply to eliminate denominators:

(x²+y²)tan(a)=(x²-y²)

Implicitly differentiate both sides

(2x+2yy')tan(a) = 2x-2yy'

Group terms and express y'(=dy/dx) in terms of x, y and tan(a) to get the required expression.

- Maths -
**abhi**, Tuesday, September 18, 2012 at 9:30amThanku soo much

**Answer this Question**

**Related Questions**

Math - Prove the identity: tanA/secA+1 = secA-1/tanA Can u please explainit to ...

Maths - Prove sqrt(Sec^2 A+Cosec^2 A)=TanA+CotA

maths - tanA/secA-1 + tanA/secA+1 = 2 cosecA

Amaths - prove sin(A+B)/sin(A-B)=(tanA+tanB)/(tanA-tanB)

Amaths - prove tanA+tanB=sin(A+B)/cosAcosB

trignometry - prove: sin(a+b)/cosacosb=tana+tanb

ARYA - IF (TANA+TANB)=M AND (TANA-TANB)=N, THEN COT(A-B)=?

Trig - prove that tanA divided by the sinA equals the secA

mathematics trignometry - if tanA=ntanX sinA=msinX then prove that cos^2A=(m^2-1...

maths trigo - prove that sin(n+1)A-sin(n-1)A/cos(n+1)A+2cos(nA)+cos(n-1)A=tanA/2